Pengamanan Pesan Teks Menggunakan Algoritma FEAL dan RSA Pada Aplikasi Android - Sri Nofrida Siregar (Journal of Computer System and Informatics (JoSYC), 2020)
Text messages are very vulnerable to the encoding or theft of information by irresponsible parties. In order to maintain the security of text messages, it can be done by using cryptographic techniques. Cryptographic techniques can encode text messages by encrypting them in the form of passwords that are not understood. The FEAL algorithm is a symmetrical block chipper type encryption algorithm, which has a block length of 64 bits, a length of 64 bits, and has an iteration of 8 rounds. The RSA algorithm is one algorithm that can be relied upon in realizing cryptographic techniques. This asymmetry algorithm will produce a higher level of security against text messages because the process is quite complicated with generation and uses different keys so that it will be difficult for cryptanalysts to access the text messages. This research will use FEAL and RSA Algorithm for the encryption and decryption process, so that in the process it is necessary to go through several long steps in order to produce the final cipher. This study describes the process of securing text messages by encoding them based on the FEAL and RSA algorithms, in the form of a password that is difficult for others to understand and understand. This is done as an effort to minimize the actions of irresponsible parties.